Order and Interpretation in Augusta Webster’s Portraits - Houston, Natalie (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractBecause Augusta Webster’s poetry involves explicit cultural critique, particularly in relation to gender ideology, it is important to turn to the textual history of her work in order to understand how these poems functioned within their original historical context. Her 1870 collection of dramatic monologues entitled Portraits foregrounds its own textual situation and the process of interpretation in its organization and material design. Read together as a collection, these poems suggest that discovering and then following a particular life path is a process of discerning, accepting, or choosing among different possibilities. Webster represents these possibilities as competing discourses, some of which are actual or imagined texts, whereas others are the ideological commonplaces of Victorian culture. Each of the speakers in Portraits explores his or her subjectivity through a process of discursive analysis and interpretation, which parallels the reading process that the structure of the volume encourages.